Corporate Agrarian Expansion and Rural Livelihood Reconfiguration: A Sociological Analysis of Agrarian Structure Transformation in Rural Maluku - Lodarmasse, Delvien; Sopamena, Junianita F.; Siwalette, Jeter D. (Jurusan Sosiologi FISIP Universitas Pattimura, 2026)
This article examines how large-scale corporate plantation expansion reconfigures agrarian structures and reshapes rural household livelihood strategies in an island context. Focusing on the entry of PT Spice Island Maluku into abaca banana plantation development in Kawa Village and its surrounding areas in West Seram Regency, this study employs a qualitative sociological case study approach. Data were collected through in-depth interviews, field observations, and document analysis of land lease agreements and village policies, involving 60 informants comprising landholding farmers, plantation laborers, customary leaders, and village officials. The findings reveal that corporate plantation expansion produces an asymmetric agrarian transformation in which formal land ownership remains with local farmers, while substantive control and land use are transferred to the corporation through long-term leasing mechanisms. This shift weakens farmers’ effective control over land, accelerates the transition from diversified subsistence agriculture to market-oriented monoculture, and compels rural households to adopt defensive livelihood strategies reliant on wage labor and residual economic activities. The novelty of this study lies in demonstrating that agrarian change does not necessarily occur through formal land dispossession, but through functional land control that generates concealed agrarian domination and new forms of economic dependency. This research contributes to agrarian and rural sociology by advancing a more nuanced understanding of non-formal land control mechanisms and by enriching empirical discussions on agrarian transformation in underrepresented island regions.